Relationship between age of allogeneic thymus donor and immunological restoration of athymic ('nude") mice. - Radov, L A (1975)
In nude mice back-crossed a minimum of five times to BALB/c, solid thymus grafts from C57Bl donors 3 days of age or younger restored both the humoral immune response against sheep erythrocytes and cellular immunity as tested by rejection of CBA skin grafts. Donor thymus placed under the renal capsule at a dose of 0-5 mg/g of recipient resulted in normal humoral immunity, while a minimum dose of 1-5 mg/g was required to reconstitute cellular competence. None of the various amounts of allogeneic thymus tissue transplanted affected the immunological status of nude recipients when grafts were obtained from donors 4 days of age or older. Histological findings correlated with the humoral and cellular responses observed. In nudes grafted with neonatal tissue, the thymus implant proliferated and developed normal architecture. The density of lymphocytes in thymus-dependent regions of peripheral lymphoid organs was near normal. On the other hand, most grafts from older (3-week-old) donors were resorbed by 90 days after implantation. In a number of cases, however, Russell bodies and numerous blast and plasma cells were seen in the graft site. Our observations suggest a possible cytotoxic rejection of implants from older allogeneic donors, while the survival and restorative capacity of transplants from 3-day-old or younger donors may have been due to a tolerogenic effect of the graft on the nude recipient.